Nutritional status, functional status, and quality of life: what is the impact and relationship on cancer patients? - Santos, Inês Miranda (2020)
Rationale and aims: Malnutrition is common and multifactorial in cancer patients (CP), combining the systemic inflammatory process with decreased food intake, loss of muscle and bone mass, and decreased functional status (FS). We aimed to track and evaluate the nutritional status (NS) of CP; associate results between hospitalized patients (HP) and day hospital patients (DHP); associate NS with tumor, symptoms, and FS. Methods: Cross-sectional observational study in HP or DHP from Garcia de Orta Hospital, over 18 years old. NS was monitored and evaluated using Nutritional Risk Screening (NRS-2002), Patient-Generated Subjective Global Assessment (PG-SGA), and anthropometric and biochemical parameters. To assess FS we used the Eastern Cooperative Oncology Group (ECOG), Karnofsky Performance Scale Index (KPSI), and handgrip dynamometer (HGD). Results: The 265 CP (114-HP, 151-DHP), of which 34.2%-HP and 17.2%-DHP had low BMI. From NRS-2002, 86.0% and 35.8% were respectively at nutritional risk. Using PG-SGA, 93.0% and 39.7% were respectively malnourished. PG-SGA were positively correlated with ECOG (p < 0.01) and negatively correlated with KPSI (p < 0.01), BMI (p < 0.01), and handgrip strength-HGS (p < 0.01-DHP and p < 0.05-HP). Conclusions: PG-SGA and FS scales are appropriate and validated tools for early identification of malnutrition and FS in CP. HGD can be a useful tool for assessing FS and NS.